Identity and Desire in John Steinbeck’s “The Harness” (1938) - Indah Damayanti (Prosiding Seminar Nasional Universitas Ma Chung, 2021)
Emma is portrayed in the nuptial relationship which situates her to be conditional upon her husband power. She seemingly portrayed as a stereotype figure of a married woman. In fact, the closely reading gives us another insight of Emma where we can see her identity from another angle. The feminist angle in literary works was regarding patriarchal society which dominates the women’s portrayal of that time. The patriarchal flourished the society’s perception which considers that is men who ruled and controlled over women. This tradition had been stumped the women desire for approval of their existence. The purpose of this paper is to analyze the female protagonist identity and her desire portrayed and focused in “The Harness.” In order to reveal Emma’s identity and her desire, the study focus not only on Emma only but also Peter is analyzed as well, analyzing the relationship between the couple. Emma appears to be strong and independent. Although she is portrayed as a little skinny old woman who lies sick most of her lifetime, she can direct Peter not only to wear the harness but also to run and keep both their house and their farm as she wants them to be. Emma, in this sense, is very powerful and “masculine” from a modern gender point of view. Her identity seemingly is far from feminine in its reality.